Application of augmented reality technology for obstetrics and gynecology teaching among undergraduates - Xuan Rao; Qian-Qian Wu; Jin Yang; Xiao Li (BMC Medical Education)
Abstract Objective The anatomy of the female reproductive system is the foundation of obstetrics and gynecology (OBGY) education. Augmented reality (AR) is now emerging information technology, which has been increasingly used in medical education of other disciplines. The present study aimed to evaluate whether AR-assisted learning mode could enhance the spatial comprehension and clinical thinking ability of undergraduates during the OBGY teaching. Methods Medical undergraduates undergoing clinical studies were enrolled. Initially, all students received traditional classroom teaching with the textbook. Subsequently, they were directed to study identical curricular content through AR software in a self-guided online format. The value of AR technology for OBGY teaching was assessed via a self-report questionnaire following completion of AR-assisted learning. Results In total, 285 valid questionnaires were collected. The AR-assisted learning mode was accepted by 99.30% students. Most students (98.60%) believed that AR-assisted learning can not only enhance their understanding of the 3D anatomy, but also help to cultivate their clinical thinking ability. Interestingly, compared with pre-class AR-assisted learning, more students accepted post-class learning (26.32% vs.73.68%). To our surprise, almost all students (98.95%) gave a positive evaluation of the AR-assisted learning mode in our study. Compared with the traditional teaching mode, we found that top advantages of AR-assisted learning mode were clearer, more intuitive and vivid (56.14%). Other perceived benefits included enhanced understanding of the spatial structure (9.47%), convenience and not limited by time and place (2.81%), and increased learning interest (2.11%). Conclusions This study is the first to demonstrate that AR technology is a valuable supplementary tool to be integrated into traditional OBGY teaching for medical undergraduates.